1985
DOI: 10.1007/bf01908187
|View full text |Cite
|
Sign up to set email alerts
|

A new device for slow progressive narrowing of vessels

Abstract: The purpose of this work was to develop a device which allows slow progressive banding of a great artery in infants within 4 to 5 weeks. Employed was the hygroscopic casein ameroid. When brought in contact with fluids, an ameroid cylinder expands characteristically. An early phase of fast expansion proceeds gradually to a phase of slow growth. Size, shape, and encasement of ameroid as well as temperature and type of surrounding fluid modify but do not alter the typical pattern of expansion. The developed const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 5 publications
1
22
1
Order By: Relevance
“…In all experiments an increase of CI was only observed during the phase of actual pressure loading and was most pronounced during slow progressive pressure loading ( fig. 3) achieved with a new device (17). A markedly increased muscle mass of RV was observed in all pigs (table 1), however, no correlation was found between muscle mass and rate of pressure increase or muscle mass and absolute increase of pressure in the right ventricle.…”
Section: Cmentioning
confidence: 86%
See 2 more Smart Citations
“…In all experiments an increase of CI was only observed during the phase of actual pressure loading and was most pronounced during slow progressive pressure loading ( fig. 3) achieved with a new device (17). A markedly increased muscle mass of RV was observed in all pigs (table 1), however, no correlation was found between muscle mass and rate of pressure increase or muscle mass and absolute increase of pressure in the right ventricle.…”
Section: Cmentioning
confidence: 86%
“…Median sternotomy and insertion of catheters into femoral or jugular veins (modified Seldinger technique) were performed under sterile conditions. Constrictors with ameroid cylinders of different sizes (17) were placed close to the bifurcation of the pulmonary artery to prevent impairment of pulmonary valve function. To facilitate easy subsequent restudies a sheath with obturator was kept in the vein.…”
Section: Preparation Of Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Others have commented that the AC currently used in treatment of PSS do not reach complete luminal closure. 11 However, to our knowledge, the current study was the first to specifically measure the rate of luminal closure of AC in the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AC undergo an initial 14 day period of rapid expansion, followed by 2 months of more gradual expansion. 23 Vascular occlusion is thought to occur by a combination of extraluminal compression and perivascular inflammation and fibrosis. 11 Research of original literature regarding the use of AC revealed that early investigators had coated the rings in petrolatum, thereby delaying water absorption and expansion of the casein ring.…”
mentioning
confidence: 99%